Mouse Umbilical Cord Mesenchymal Stem Cell Paracrine Alleviates Renal Fibrosis in Diabetic Nephropathy by Reducing Myofibroblast Transdifferentiation and Cell Proliferation and Upregulating MMPs in Mesangial Cells. (5th May 2020) - Li, Hongde; Rong, Pengfei; Ma, Xiaoqian; Nie, Wei; Chen, Yan; Zhang, Juan; Dong, Qiong; Yang, Min; Wang, Wei
Abstract : Transplantation of umbilical cord mesenchymal stem cells (UC-MSCs) is currently considered a novel therapeutic strategy for diabetic nephropathy (DN). However, the mechanisms by which UC-MSCs ameliorate renal fibrosis in DN are not well understood. Herein, we firstly investigated the therapeutic effects of mouse UC-MSC infusion on kidney structural and functional impairment in streptozotocin- (STZ-) induced diabetic mice. We found that the repeated injection with mUC-MSCs alleviates albuminuria, glomerulus injury, and fibrosis in DN mouse models. Next, mesangial cells were exposed to 5.6 mM glucose, 30 mM glucose, or mUC-MSC-conditioned medium, and then we performed western blotting, immunofluorescence, wound healing assay, and cell proliferation assay to measure extracellular matrix (ECM) proteins and matrix metalloproteinases (MMPs), myofibroblast transdifferentiation (MFT), and cell proliferation. We demonstrated that mUC-MSC paracrine decreased the deposition of fibronectin and collagen I by inhibiting TGF- β 1-triggered MFT and cell proliferation mediated by PI3K/Akt and MAPK signaling pathways, and elevating the levels of MMP2 and MMP9. Importantly, we provided evidence that the antifibrosis role of mUC-MSC paracrine in DN might be determined by exosomes shed by MSCs. Together, these findings reveal the mechanisms underlying the therapeutic effects of UC-MSCs on renal fibrosis in DN and provide the evidence for DN cell-free therapy based on UC-MSCs in the future.